2008
DOI: 10.2527/jas.2007-0057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processed grains on fecal pH, starch concentration, and shedding of Escherichia coli O157 in feedlot cattle1

Abstract: Manipulation of cattle diets has been proposed as a possible preharvest control measure for Escherichia coli O157. Altering hindgut fermentation through diet changes may be a means to reduce fecal shedding of E. coli O157. In Exp. 1, the objective was to determine whether fecal shedding of E. coli O157 was related to fecal starch concentration. Beginning on d 20, and every week thereafter until d 61, steers in 54 pens (6 to 7 steers per pen) were sampled (n = 122) by fecal collection and rectoanal mucosal swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
2
19
0
5
Order By: Relevance
“…Depenbusch et al (2008) also found that fecal pH is negatively correlated with FSC, even though the correlation coefficient was lower (-0.34). Dry matter intake was positively correlated (p ≤ 0.05; PCC = 0.23) with FSC, agreeing with the results reported by Galyean et al (1979).…”
Section: Resultsmentioning
confidence: 86%
“…Depenbusch et al (2008) also found that fecal pH is negatively correlated with FSC, even though the correlation coefficient was lower (-0.34). Dry matter intake was positively correlated (p ≤ 0.05; PCC = 0.23) with FSC, agreeing with the results reported by Galyean et al (1979).…”
Section: Resultsmentioning
confidence: 86%
“…Yeasts in the diet remove the oxygen in the viable cellulolytic bacteria which use lactic acid and a pH decrease of the ruminal contents occurs (Wallace, 2004). Fecal pH has an inversely proportional behavior to rumen degradation and fecal excretion of starch, as reported by Barajas and Zinn (1998) and Depenbusch et al (2008). Therefore, in diets with high grain inclusion, a greater quantity of starch does not undergo rumen fermentation and more starch passes through the small intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Estes autores também observaram que animais alimentados com grãos destilados, mas sem a inclusão de feno de alfafa apresentaram carcaças mais leves e magras em relação àqueles novilhos alimentados com 6% de feno de alfafa. Marques et al (2011) ao avaliar a utilização de grão de milho inteiro e a inclusão de três níveis de bagaço de cana-de-açúcar in natura (0, 3 ou 6% na MS da ração total) pode observar efeito quadrático de inclusão de bagaço para consumo de MS, ganho médio diário e peso de carcaça quente. Entretanto o desempenho de bovinos alimentados sem inclusão de bagaço foi inferior aqueles animais recebendo dietas com 3 ou 6% de bagaço.…”
Section: Introductionunclassified
“…MacDonald et al (2011) ao utilizar dietas a base de milho floculado, com inclusões de feno de alfafa de 7,5, 10 ou 12,5% e 25% de grãos de sorgo destilados, concluíram que com o aumento da inclusão de feno de alfafa houve tendência em aumentar linearmente o consumo de MS e a conversão alimentar.…”
Section: Introductionunclassified
See 1 more Smart Citation